Implementasi Maqashid Syariah Dalam Pelayanan Custumer Service Bank Syariah (Studi Pada BNI Syariah KC Medan) - Supaino Supaino (Universitas Islam Sumatera Utara, 2020)
AbstractMaqashid al-sharia consists of two, namely maqaṣid and sharia. Maqashid means intention or purpose. The purpose (maqashid) can be achieved by means of taklif, and its implementation depends on the ability to understand the main sources of law, both Al-Qur'an and hadith.The purpose of this research with the title the implementation of maqhasid sharia in services at Bank Negara Indonesia Syariah Medan Branch is to see the implementation of services in Islamic banking in the field of customer service. The research was conducted at BNI Syariah Medan. This type of research is descriptive qualitative. Data collection methods in the research are using library research, observation and interviews. The sampling technique used random sampling. The types of data used in this study are primary and secondary data. The data analysis used in this study was descriptive by using literature studies in the form of muamalah fiqh books.The results showed that the implementation of maqashid sharia in services at Bank Negara Indonesia Syariah Medan Branch is appropriate, based on the indicators of educating the individuals (Tahzibul Fardh), upholding justice (Iqamah al-adl), and achieving prosperity (Maslahah).Keywords: Service, Maqashid sharia, Customer Service